Capacitación y posición social de los empleados públicos de la ciudad de México a comienzos del siglo XX - Barbosa Cruz, Mario (El Colegio de México, A.C., 2018)
In the second half of the 19th Century, there was an increase in the number of schools and administrative training programs for public servants. This responded to the needs of a growing bureaucracy in Mexico’s capital. This article analyzes the extent to which these schools fed the bureaucracy and allowed for the upward social mobility of those who wished to become public servants in Mexico City, exploring marks of distinction such as social position, identification as being middle class, jobs held and the appearance of Mexico City public servants in the first three decades of the 20th Century.